Optimization Of Cassava Leaf (Manhihot esculenta Crantz) and Grape Seed Oil (Vitis vinifera L.) Formula Using Simplex Lattice Design Method - Tanjung, Salsabila Adelia; Suswidiantoro, Vicko; Dwiningrum, Riza (LPPM Universitas Dhyana Pura, 2025)
The use of natural ingredients in skincare products is increasingly being developed due to their perceived safety and environmental friendliness compared to synthetic chemicals. Cassava leaves (Manihot esculenta Crantz) contain flavonoids, saponins, tannins, and triterpenoids, which function as natural antioxidants. These compounds help protect the skin from free radicals and maintain skin health. Meanwhile, grape seed oil (Vitis vinifera L.) is rich in linoleic acid, which acts as a natural moisturizer and helps maintain the function of the skin’s epidermal barrier. The combination of these two ingredients has the potential to produce high-quality liquid soap. This study aims to optimize the liquid soap formulation using cassava leaf extract and grape seed oil through the Simplex Lattice Design (SLD) method. The research was conducted by designing five formulations with varying concentrations, followed by evaluation based on physical parameters such as organoleptic properties, homogeneity, pH, foam height, viscosity, and formulation stability. The results showed that increasing the concentration of cassava leaf extract raised the viscosity, while grape seed oil tended to reduce foam height. The optimal formula was obtained using Design Expert software with a desirability value of 1.000, and predicted values of pH 8.33, foam height of 147 mm, and viscosity of 663 cPs. Verification results confirmed the agreement between predicted and actual values. It can be concluded that the combination of cassava leaf extract and grape seed oil can produce a stable, high-quality liquid soap formulation that meets physical quality standards